2009
DOI: 10.1111/j.1365-2494.2009.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of lambs offered Italian ryegrass (Lolium multiflorum L.) and barley (Hordeum vulgare L.) herbage as choices

Abstract: Partial preference for feeds in ruminants is a welldocumented phenomenon although their explanation can be elusive. The hypothesis was tested that sheep offered herbage of two annual grass species differing in chemical composition free-choice would select a diet that would maximize the nutritive value of the diet compared with sheep offered each herbage separately through a greater nutrient balance and synchronization of nutrient release for efficient ruminal microbial function. Fifteen male lambs were placed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
5
2
Order By: Relevance
“…(2015) (73.07 for fresh ryegrass vs. 73.01 for ryegrass silage). Values of DM digestibility for fresh ryegrass and ryegrass silage were higher than those reported by Catanese et al (2009), Zhang et al (1995 and Ohshima et al (1988), while it was lower than those obtained by Amaral et al (2011) and Nishino et al (1995). The results may be due to the difference in harvest season and silage process.…”
Section: Digestibilitycontrasting
confidence: 53%
“…(2015) (73.07 for fresh ryegrass vs. 73.01 for ryegrass silage). Values of DM digestibility for fresh ryegrass and ryegrass silage were higher than those reported by Catanese et al (2009), Zhang et al (1995 and Ohshima et al (1988), while it was lower than those obtained by Amaral et al (2011) and Nishino et al (1995). The results may be due to the difference in harvest season and silage process.…”
Section: Digestibilitycontrasting
confidence: 53%
“…While HV has 15%-17% of CP (Balabanli 2009), AR also has CP contents of around the same values (Ozkul et al 2012). These CPRs and yields of sole AR sowings were reported as between 7.3%-25.4% and 101-5197 kg ha -1 , respectively (Parlak et al 2007;Gultekin 2008;Catanese et al 2009;Simic et al 2009;Kusvuran 2011;Durst et al 2013;Rivera et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…It is generally a highly nutritious grass that may be presented as forage for beef cattle through grazing, dried out and fed as hay, or ensiled and fed as silage (Acikgoz 2001;Kusvuran and Tansi 2011;Durst et al 2013), and desirably eaten by livestock, especially in milk production (Kusvuran 2011). In recent years, one of the cultivars of AR, 'Caramba', has quite well adapted to Turkey's climate and soil conditions (Ozkul 2012), which has been recognized as potential roughage for ruminant animals (Van Niekerk et al 2008;Catanese et al 2009). Furthermore, (Ozkul et al 2012) reported that it will rise crucially in the use and importance of AR in future and it will be preferred by livestock as a sole crop when compared to cereals such as barley and triticosecale (Van Niekerk et al 2008;Catanese et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although generally it is used in ruminant feeding by pasturing or harvesting in the form of fresh grass, caramba may be used after it is dried or ensilaged ( Hannaway et al, 1999 ; Bernard et al, 2002 ; Shao et al, 2005 ; Cooke et al, 2008 ). The conducted studies showed that Italian ryegrasses have high (71% to 78%) dry matter (DM) digestibility ( Ohshima et al, 1988 ; Catanese et al, 2009 ; Amaral et al, 2011 ) and have a favorable effect on milk yield and composition ( Mccormick et al, 1990 ;1998; Miller et al, 2001 ; Bernard, 2003 ) and increase the live weight of livestock ( De Villiers et al, 2002 ; Zaman et al, 2002 ; Van Niekerk et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%